Impact of ischemic lesion on sleep related connectivity in the sensorimotor cortex - Canu, Maria Giovanna; Barban, Federico; Chiappalone, Michela; Arnulfo, Gabriele; Cota, Vinícius Rosa (Frontiers in Neuroscience, 2025)
Ischemic events can cause cell death and tissue loss, leading to the impairment of neural circuitry by disconnection of its neural substrates. However, the highly plastic properties of the nervous system can provide recovery by boosting circuital redundancies or triggering functional adaptation/repurposing of closely related networks. In this context, understanding how ischemic brain lesions reorganize circuits directly or indirectly connected to the injury site is crucial for developing therapeutic approaches, particularly neuroprostheses based on neurostimulation for brain-rewiring. Furthermore, it is also fundamental to consider the sleep–wake cycle in such an inquiry, considering its well-established role as bearer of key mechanisms of neuroplasticity. This study aimed to investigate how an ischemic lesion in the rat’s primary motor cortex affects the connectivity of areas involved in the sensorimotor loop, specifically the premotor cortex (RFA) and the primary somatosensory cortex (S1), during sleep. We analyzed Local Field Potentials recorded during slow-wave sleep in rats with and without ischemic lesions. Functional connectivity and cross-frequency interactions were quantified using Phase Locking Value (PLV) and Phase-Amplitude Coupling (PAC) analyses, respectively. Our findings revealed a marked increase in PAC 7 days after the lesion, followed by a partial return toward baseline levels at 14 days post-lesion. These results suggest a transient reorganization of network dynamics associated with early recovery processes. The observed changes provide insights into spontaneous post-stroke plasticity during sleep and identify potential electrophysiological biomarkers of recovery. Our findings may contribute to the design of sleep-integrated neurostimulation strategies to promote motor rehabilitation after stroke.